Comparison of treatment costs of grade 3/4 adverse events associated with erlotinib or pemetrexed maintenance therapy for patients with advanced non-small-cell lung cancer (NSCLC) in Germany, France, Italy, and Spain - Banz, Kurt; Bischoff, Helge; Brunner, Matthias; Chouaid, Christos; Castro Carpeño, Javier de; Marinis, Filippo de; Grossi, Francesco; Vergnenègre, Alain; Walzer, Stefan (Lung cancer, 2011)
Objective of this indirect economic comparison was to estimate and compare management costs of grade 3/4 adverse events (AEs) reported for first-line erlotinib or pemetrexed maintenance therapy in patients with advanced non-small cell lung cancer (NSCLC). The economic analysis was performed for Germany, France, Italy and Spain. Types and incidences of reported grade 3/4 AEs observed with erlotinib or pemetrexed maintenance therapy were retrieved from two recently published placebo-controlled trials. Country-specific estimates on standard treatment algorithms and incremental medical resource utilization associated with each of the reported grade 3/4 AEs have been obtained from clinical oncologists practicing in the four countries and co-authoring this article. The resource use items were subsequently assigned country-specific tariffs to estimate total per-patients costs associated with the AE profiles of the two compared maintenance regimens. For the economic analysis a customized economic spreadsheet model was employed. Our comparison shows lower total average per-patient AE management costs for erlotinib than for pemetrexed maintenance therapy in all four studied countries. Total estimated cost savings per patient in favour of erlotinib amount to € 121, € 237, € 106, and € 119 for Germany, France, Italy and Spain, respectively. These AE cost savings for erlotinib when compared to pemetrexed represent a decrease by 80%, 71%, 94%, and 82%, respectively. The study also discovered considerable differences in AE management costs across countries which are primarily due to differences in clinician's estimates of hospitalization referral rates. Erlotinib maintenance therapy in patients with advanced NSCLC causes lower AE management costs than pemetrexed maintenance therapy indicating a potentially superior tolerability profile.
Gesehen am 17.02.2022